Plano de marketing digital em bibliotecas universitárias: modelo e estratégias propostas à Biblioteca Central da UFAM - Silva, Kamilla Pereira (2024)
It proposes the creation of a Digital Marketing plan for the Central Library of the Federal University of Amazonas. The capstone aims to present different Digital Marketing strategies that will enable the creation of a model plan for the UFAM Central Library. In order to achieve this general objective, the following specific objectives were carried out: identifying the profile and needs of the UFAM Central Library in relation to the use of digital Marketing strategies; checking the literature for the best digital Marketing strategies for creating a Marketing plan for university libraries and, finally, proposing the creation of a Digital Marketing Plan model aligned with the reality of this library. Methodologically, the research is classified as exploratory, bibliographical, descriptive and documental, aiming to deepen knowledge about Digital Marketing strategies applicable to the context of university libraries. It results in the identification of 8 effective strategies that can be implemented to improve communication, engagement and the dissemination of resources at the UFAM Central Library. Finally, it is hoped that the proposal will contribute to expanding access to and use of information resources, satisfying the information needs of the academic community and promoting the library as a space for continuous learning and innovation.